Long-term survival after multidisciplinary therapy for residual gallbladder cancer with peritoneal dissemination: a case report - Daisuke Kuga; Tomoki Ebata; Yukihiro Yokoyama; Tsuyoshi Igami; Gen Sugawara; Takashi Mizuno; Junpei Yamaguchi; Masato Nagino (Surgical Case Reports)
Abstract Background Although surgical resection is the only curative treatment for gallbladder cancer (GBC), concomitant peritoneal dissemination is considered far beyond the scope of resection. We report a long-term survivor with a residual GBC with multiple peritoneal disseminations who underwent an extended resection after effective chemotherapy. Case presentation A 59-year-old male underwent an open cholecystectomy for Mirizzi syndrome at a local hospital. Because of severe inflammation, the gallbladder was perforated during surgery, ending in a piecemeal resection. A pathological examination revealed GBC with positive margins, and the patient was referred to our hospital 1 month after surgery for further treatment. A multidetector-row computed tomography (MDCT) showed three hypoattenuated tumours: a tumour (3.9 cm) at the left medial segment corresponding to the gallbladder bed, a tumour (1.8 cm) around the hepatic flexure of the transverse colon, and a tumour (1.0 cm) at the stump of the cystic duct. Percutaneous needle biopsy was performed, which provided histologic evidence of adenocarcinoma. Thus, the patient had a rapidly progressive local relapse with limited peritoneal dissemination, labelled ycT3N0M1, stage IVB disease according to the UICC system. After the administration of 3 cycles of gemcitabine plus cisplatin combination chemotherapy, the size of all tumours and the CA19-9 level decreased significantly. Since the patient’s general condition and liver function reserve were satisfactory, we decided the initial unresectable scenario to perform surgical therapy. After portal vein embolization, right hepatectomy, resection of the extrahepatic bile duct, partial duodenectomy, and partial colectomy were performed. Operative time was 555 min, and intraoperative blood loss was 1654 mL. Pathologic diagnosis of residual gallbladder carcinoma with peritoneal dissemination was confirmed, and the surgical margins were tumour-free. The patient was discharged on postoperative day 29, with a Clavien-Dindo IIIa complication (abdominal wall abscess). Postoperative adjuvant chemotherapy with tegafur/gimeracil/oteracil was administered during 1 year after surgery. The patient is doing well 6 years after the second surgery without evidence of disease. Conclusions Although specific clinical factors were associated with a favourable outcome in this patient, the present report suggests that multidisciplinary therapy may be a promising option in selected patients with distant metastatic GBC.